Land ecological protection polices improve ecosystem services: A case study of Lishui, China - Tang, Yisheng; Tang, Jinghao; Yu, Xianghong; Qiu, Lefeng; Wang, Jingyi; Hou, Xianrui; Chen, Dongxiang (Frontiers in Environmental Science, 2022)
Ecological priority and green development have become the main theme of the times in China. The policy performance evaluation of ecological protection needs to quantitatively identify the changes of ecosystem quality and services firstly. This paper constructed the analytical framework driven by ecological protection policy of " Goal-oriented – Policy driven – Ecological quality– Service improvement ", and used multi-source data to establish the evaluation approach of "ecosystem quality-ecosystem services- ecosystem services value". This study took Lishui as a case study to confirm the framework proposed. The results show that the ecosystem quality of Lishui has been steadily improved in recent ten years. The overall quality of ecosystem services such as vegetation oxygen release, carbon sequestration, pollution removal, cooling service, humidification regulation and water conservation service has been improved by a range of 2-6%. The value of ecological products has increased from 143.28 billion CNY in 2009 to 150.23 billion CNY in 2019. Lishui has implemented the development concept of "ecological civilization", and the policies of ecological restoration or land remediation have changed land use and ecosystem quality, which was the main driving force for the improvement of ecological quality and the main promotion of ecological products value. The methods and results can provide insight into the impact of land policies on ecosystem services and decisions that support for further optimizing land ecological protection policies.